2021
DOI: 10.3390/su13020831
|View full text |Cite
|
Sign up to set email alerts
|

Cashless Transactions: A Study on Intention and Adoption of e-Wallets

Abstract: This study explored the effect of perceived usefulness, perceived ease of use, social influence, facilitating condition, lifestyle compatibility, and perceived trust on both the intention to use an e-wallet and the adoption of an e-wallet among adults by using the unified theory of acceptance and use of technology (UTAUT). This quantitative study adopted a cross-sectional research design to gather data from 501 respondents using a Google Form. The collected data were analyzed using partial least square structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
183
4
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(295 citation statements)
references
References 45 publications
42
183
4
4
Order By: Relevance
“…Numerous antecedent variables were applied to predict the adoption of technology in previous studies in which they have found that among the factors were perceived usefulness (Yang et al, 2021;Intarot, 2018;Shankar & Datta, 2018;Mun et al, 2017;Sidek, 2015;Akturan & Tezcan, 2012), perceived ease of use (Yang et al, 2021;Chawla & Joshi, 2020;Grover, Kar, & Janssen, 2019;Ilavarasan Mehrad & Mohammadi, 2017;Roy & Sinha, 2017;Trivedi, 2016), perceived security (Wong & Mo, 2019;Batra & Kalra, 2016;Varsha & Thulasiram, 2016;Liu et al, 2012) and subjective norms (Sarika & Vasantha, 2019;Lwoga & Lwoga, 2017;Cao, et al, 2016;Oliveira et al, 2016;Amoroso & Magnier, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous antecedent variables were applied to predict the adoption of technology in previous studies in which they have found that among the factors were perceived usefulness (Yang et al, 2021;Intarot, 2018;Shankar & Datta, 2018;Mun et al, 2017;Sidek, 2015;Akturan & Tezcan, 2012), perceived ease of use (Yang et al, 2021;Chawla & Joshi, 2020;Grover, Kar, & Janssen, 2019;Ilavarasan Mehrad & Mohammadi, 2017;Roy & Sinha, 2017;Trivedi, 2016), perceived security (Wong & Mo, 2019;Batra & Kalra, 2016;Varsha & Thulasiram, 2016;Liu et al, 2012) and subjective norms (Sarika & Vasantha, 2019;Lwoga & Lwoga, 2017;Cao, et al, 2016;Oliveira et al, 2016;Amoroso & Magnier, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There was an increase in online transactions and the use of FDAs as a result of the measures adopting the use of cashless transactions for the purchase of goods and services to avoid direct contact between people [14][15][16]. The consumption and the transaction habits have accelerated from the traditional cash and in-store services towards online-to-offline services, facilitated by online payment platforms and applications, including FDAs.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that with such changes, it is important to mention that with such electronic transactions, personal information and the monetary transaction being shared. based on that, some scholars mentioned that there is a need more than before to focus more on the consumer protection, privacy, security and trust that is related to use e-payment transactions (Bashir et al, 2021;Yang et al, 2021). For example, trust is essential for efficient interactions and secure payments in online interactions conducted in electronic commerce (e-commerce) systems, as online interactions lack the face-to-face interface (Al-Dala'in et al, 2009;Ameen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%